Analysis of Mathematics Learning Outcomes for High School Students Accepted Based on The Zoning System - Mustamin Idris; Dasa Ismaimuza; Bakri Mallo; Ahmad Ahmad (Sustainable, 2023)
The purpose study is to analyze mathematics learning outcomes based on three zones, zone 1: SMA 1, zone 2: SMA 2, and zone 3: SMA 3. Class XI students were research objects taken from each zonation with a total sample of 155 for zone 1, 116 for zone 2, and 116 for zone 3, a total is 387 students. The results showed that the average mathematics learning outcomes for SMA Palu students based on zoning, namely zone 1, zone 2, and zone 3, obtained a score of 83.71, above the KKM. The test results of the analysis of variance in mathematics learning outcomes at Palu City High School based on Zone 1, Zone 2, and Zone 3 did not have a significant difference, which means that the ability levels of the three zones have the same mathematics learning outcomes. This result is due to the implementation of PPDB with a zoning system that can distribute new students well based on the zonation setting in the High School education unit in Palu, especially the distance between where they live and school. Conclude that the process of admitting new students with a zoning system was successfully carried out based on the criteria set by the Government and Department of Education for the 2021/2022 school year.